Mikro- i makrostruktura słownika neologizmów Obserwatorium Językowego Uniwersytetu Warszawskiego - Katarzyna Kłosińska (LingVaria)
MICRO- AND MACRO-STRUCTURE OF THE DICTIONARY OF NEOLOGISMS OF THE LANGUAGE OBSERVATORY OF THE UNIVERSITY OF WARSAW